Tamak Dalam Perspektif Hadis - Tahir, Muhyiddin (Fakultas Adab dan Humaniora UIN Alauddin, 2013)
Greedy is a desire in oneâs self to get more than what he or she has had for their own sake. Greedy is a very bad attitude. The desire to get and collect wealth is not forbidden as long as the wealth is earned based on Islamic teaching. In addition, the wealth is not only for him or her but for others in terms of social activity as well. How is greedy perceived in the view of hadits? And what are its effects on live? This paper provides an answer to every aspects of greedy which is a very bad attitude.Â